2015
DOI: 10.1074/jbc.m115.674382
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal Cytosolic Region of Rim21 Senses Alterations in Plasma Membrane Lipid Composition

Abstract: Yeast responds to alterations in plasma membrane lipid asymmetry and external alkalization via the sensor protein Rim21 in the Rim101 pathway. However, the sensing mechanism used by Rim21 remains unclear. Here, we found that the C-terminal cytosolic domain of Rim21 (Rim21C) fused with GFP was associated with the plasma membrane under normal conditions but dissociated upon alterations in lipid asymmetry or external alkalization. This indicates that Rim21C contains a sensor motif. Rim21C contains multiple cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…In that previous study, we showed that GFP-Rim21C was associated with the PM and the yeast bud neck, where lipid asymmetry is altered locally [13] in WT cells under normal conditions, whereas it dissociated from the PM upon activation of the Rim101 pathway (under alkali conditions or in cells with mutations in lipid translocases) [22] (see also Fig. 3D).…”
Section: Disruption Of Er-pm Contact Causes Constitutive Activation Omentioning
confidence: 85%
See 3 more Smart Citations
“…In that previous study, we showed that GFP-Rim21C was associated with the PM and the yeast bud neck, where lipid asymmetry is altered locally [13] in WT cells under normal conditions, whereas it dissociated from the PM upon activation of the Rim101 pathway (under alkali conditions or in cells with mutations in lipid translocases) [22] (see also Fig. 3D).…”
Section: Disruption Of Er-pm Contact Causes Constitutive Activation Omentioning
confidence: 85%
“…The amplified fragments were inserted directly into the chromosome by homologous recombination. Integration of P ADH -GFP-RIM21C to the yeast chromosome was performed as described previously [22]. Successful deletions of the genes and tagging were confirmed by genomic PCR and/or fluorescence microscopy.…”
Section: Genetic Manipulation and Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…This activation is dependent on Rim21, suggesting that plasma membrane depolarization is a key signal sensed by Rim21 (160). Moreover, a recent study suggests that alterations in lipid asymmetry cause changes in lipid composition and local charge on the inner leaflet, leading to dissociation of the Rim21 complex from the plasma membrane and recruitment of downstream proteins (161). Thus Rim21 senses external alkalization, as well as altered lipid asymmetry.…”
Section: Adapting To Individual Stressesmentioning
confidence: 99%